2019
DOI: 10.1186/s12970-019-0281-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a polysaccharide-based multi-ingredient supplement on salivary immunity in non-elite marathon runners

Abstract: BackgroundExtreme exercise may alter the innate immune system. Glycans are involved in several biological processes including immune system regulation. However, limited data regarding the impact of glycan supplementation on immunological parameters after strenuous exercise are available. We aimed to determine the impact of a standardized polysaccharide-based multi-ingredient supplement, Advanced Ambrotose© complex powder (AA) on salivary secretory Immunoglobulin A (sIgA) and pro- and anti-inflammatory protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Sixth, corrections for plasma volume change that can occur following an acute bout of exercise has been recommended when studying serum biomarkers (Kargotich et al, 1997); however, this does not apply to all published studies (Neidhart et al, 2000;Kersting et al, 2005;Mündermann et al, 2005;Niehoff et al, 2011). Immediate and 48-h post-marathon plasma volume change determined with haemoglobin and haematocrit data of a previous study of our group (Roca et al, 2019) in 41 runners of 2016 Barcelona Marathon was −1.2 and −1.7%, respectively. The percentage of biomarker change when correcting for plasma volume is small, and we believe it would apply to our study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sixth, corrections for plasma volume change that can occur following an acute bout of exercise has been recommended when studying serum biomarkers (Kargotich et al, 1997); however, this does not apply to all published studies (Neidhart et al, 2000;Kersting et al, 2005;Mündermann et al, 2005;Niehoff et al, 2011). Immediate and 48-h post-marathon plasma volume change determined with haemoglobin and haematocrit data of a previous study of our group (Roca et al, 2019) in 41 runners of 2016 Barcelona Marathon was −1.2 and −1.7%, respectively. The percentage of biomarker change when correcting for plasma volume is small, and we believe it would apply to our study.…”
Section: Discussionmentioning
confidence: 98%
“…We examined the dynamics of a panel of inflammatory, high-energy, and cartilage biomarkers in non-elite athletes completing the Barcelona Marathon in 2017. These new data were recorded as part of the SUMMIT Project, whose main goal is analysing health risk in the population engaged in high-intensity physical activities (Maqueda et al, 2017;Roca et al, 2017Roca et al, , 2019Nescolarde et al, 2020). The procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation (institutional and national) and with the Helsinki Declaration of 1975, as revised in 2000.…”
Section: Methodsmentioning
confidence: 99%
“…This study showed that short-term changes in daily movement behavior could significantly affect sCRP levels in a way that increased steps per day can decrease sCRP levels and vice versa. Moreover, as shown by Roca et al ( 98 ) in a sample of 41 male marathon runners sCRP levels significantly increased 48 hours after marathon.…”
Section: Resultsmentioning
confidence: 53%
“…For example, Ambrotose glyconutrients have been associated with improvements in memory and subjective ratings of well-being in numerous studies [4,5,15,16]. With regards to immune modulation, marathon runners ingesting Advanced Ambrotose daily for 15 days prior to competition exhibited lower resting salivary chemokines, Gro-alpha and Gro-beta, compared to nonsupplemented counterparts; however, supplemented runners did not experience a reduction in these markers after exercise but did experience a reduction in the salivary chemokine, angiogenin, after exercise [17]. Alternatively, Ambrotose glyconutrients can also be offered with added antioxidants (Ambrotose AO).…”
Section: Discussionmentioning
confidence: 99%